2018
DOI: 10.1371/journal.pone.0208152
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic shape and volume abnormalities in female patients with panic disorder

Abstract: The thalamus is believed to play crucial role in processing viscero-sensory information, and regulating the activity of amygdala in patients with panic disorder (PD). Previous functional neuroimaging studies have detected abnormal activation in the thalamus in patients with PD compared with healthy control subjects (HC). Very few studies, however, have investigated for volumetric abnormalities in the thalamus in patients with PD. Furthermore, to the best of our knowledge, no previous study has investigated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Studies have indicated that the VA has anatomical and functional connections with the rest of the thalamic nuclei and regions within the frontolimbic circuit, namely the basal ganglia and prefrontal cortices ( McFarland and Haber, 2002 ; Grodd et al. , 2020 ), and is thus thought to be an important center for executive and motor functioning as well as reward and emotion processing ( Xiao and Barbas, 2002 , 2004 ; Child and Benarroch, 2013 ; Asami et al. , 2018 ; Wolff and Vann, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the VA has anatomical and functional connections with the rest of the thalamic nuclei and regions within the frontolimbic circuit, namely the basal ganglia and prefrontal cortices ( McFarland and Haber, 2002 ; Grodd et al. , 2020 ), and is thus thought to be an important center for executive and motor functioning as well as reward and emotion processing ( Xiao and Barbas, 2002 , 2004 ; Child and Benarroch, 2013 ; Asami et al. , 2018 ; Wolff and Vann, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ventral thalamic changes also corresponded with neuropsychiatric symptoms. The involvement of the ventral thalamus in neuropsychiatric symptoms has been found in anxiety, panic disorders, and schizophrenia [38,39]. In particular, schizophrenia has been shown to be associated with lesser neurons in the left ventrolateral posterior nucleus, but not the right [38].…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, the activation of cannabinoid receptor type-1 (CB1 receptor) in the telencephalon decreased anxiety from acute restraint stress [ 78 ]. Pharmacological activation of the GABAergic system in the telencephalon also reduced the anxiety levels of Japanese medaka [ 79 ]. The thalamus consists of several nuclei and is involved in various functions, including the regulation of anxiety and fear in humans [ 80 ].…”
Section: Discussionmentioning
confidence: 99%